Bi-atrial myxomas presenting as recurrent pulmonary emboli in a girl. Issue 700 (February 1984) - Hanly, J.; de Buitleir, M.; Shaw, K.; Maurer, B.; FitzGerald, M. X.
Abstract : A 14-year-old girl whose sole presenting features were symptoms of pulmonary embolism, was found to have bi-atrial myxomas. The diagnosis was made preoperatively, and the patient had a successful outcome following elective surgery. The absence of other features such as systemic embolism, atrioventricular valvular obstruction, fever and constitutional symptoms makes this a most unusual case. Right atrial myxoma should be considered in any patient presenting with pulmonary embolism for which there is no obvious source.